Characterization and Quantitation of Experimental Surgical-Wound Infections Used to Evaluate Topical Antibacterial Agents - McRipley, R. J. (1976)
Reproducible experimental surgical-wound infections in mice for use in the evaluation of topical antibacterial agents are described. The experimental would was created on the backs of mice by means of a midline incision and was infected by means of cotton sutures monocontaminated with Staphylococcus aureus or Pseudomonas aeruginosa. The course of these wound infections was followed by quantitation of surface bacteria through use of a surface rinse technique. Surface wound counts of the infecting organisms thus obtained appeared to reflect the dynamics of the total wound count, as determined by homogenization of biopsied tissue. Treatment of infected wounds with a placebo cream had only a slight effect on surface wound counts and on mortality in the case of the S. aureus infection but enhanced markedly the lethality of the P. aeruginosa infection.